Lateral flow immunoassay for long forms of cardiac troponin T using upconversion luminescence - Haataja, Sofia (My University, 2025)
Cardiac troponins (cTns) are essential biomarkers for diagnosing acute myocardial infarction (AMI). However, conventional cTn assays often lack specificity, as elevated troponin levels can also occur in conditions unrelated to AMI. Cardiac troponin T (cTnT) gradually fragments over time in the bloodstream. Recent studies show that long forms of cTnT are predominant in early AMI, while shorter fragments are more common in non-cardiac conditions. Therefore, long cTnT has been identified as a more specific AMI biomarker. Rapid AMI detection is critical in reducing heart damage and improving patient outcomes, highlighting the need for fast point-of-care (POC) tests. This study aimed to develop a lateral flow immunoassay (LFIA) utilizing upconverting nanoparticles (UCNPs) for rapid and sensitive detection of long cTnT. To achieve this, the experimental protocol and key parameters for cTnT-LFIA performance were established, including the test strip structure, wash buffer composition, and incubation times. Integration of a passive flow control component was also explored. Analytical performance was characterized by the limit of detection (LoD) in spiked lithium-heparin plasma, calculated as the mean plus 3x the standard deviation of a non-spiked sample. Clinical performance was evaluated by correlation analysis to an established reference assay for long cTnT using patient samples (n=5). The LFIA reached an LoD of 21.99 ng/L, with a strong sigmoidal correlation between upconversion luminescence (UCL) signal and analyte concentration (R²=0.99) across a wide analytical range (0–30 000 ng/L in spiked plasma). The coefficient of variation (CV) dropped below 20 % at concentrations ≥100 ng/L. In patient samples, the LFIA strongly correlated with the reference assay (r=0.95). These results demonstrate that the long cTnT UCL-LFIA enables rapid (30-minute) and sensitive long cTnT detection, representing a promising step towards more specific AMI detection in POC diagnostics.
Keywords: acute myocardial infarction, cardiac biomarkers, cardiac troponin T, lateral flow immunoassay, upconverting nanoparticles, point-of-care testing